Actualizing the Phrase "Please Be Happy There Is An Exam" in the Tembang Exam - Indriani, Puspita; Amri, Miftachul; Sodiq, Syamsul (Proceeding Series of International Conference on Arts and Humanities, 2021)
The purpose of this study is to describe how a nembang exam could be fun, and the assessment result shows information about students’ competencies validly. This is a qualitative descriptive study. Analysis was done by describing the data. Data was collected through forms spreading to get primary data and observation throughout the exam to get secondary data. Results of this study shows that practical exam is efficient regarding the implementation and the financing. From the reliability of the students and the examiners, the exam could be held well except for the reliability of the text item because of the form of the Tembang. Validity of the exam was shown in how the result of the exam was directly given to the students after the correction process using the theory of constructing Tembang Macapat. The authenticity was shown in the topic choice of the Tembang, which was near with the students despite that the students were not familiar with using them.